Endosonography: New Developments in 2006 - Marc Giovannini (The Scientific World Journal, 2007)
Recent progress of the data processing applied to ultrasound (US) examination made it possible to develop new software. The US workstation of the last generation thus incorporated a computer into their center that allowed a very precise treatment of the US image. This made it possible to work out new images like three-dimensional (3-D) US, the US of contrast-harmonic associated with the intravenous injection with product with contrast for US, and finally even more recently, elastography. These techniques, currently quite elaborate in percutaneous US, are to be adapted and evaluated with echoendoscopy (EUS).